(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Presents reviews of the work of local and foreign scientists on the importance of studying the agrochemical properties of the soil in determining the rate of pomegranate fertilization, and the pomegranate’s demand for fertilizer. Information about the soilclimatic conditions of the research object is given and the results obtained on agrochemical properties are described. Recommendations on fertilization periods and norms are presented, taking into account the agrochemical properties of the soil.